Development of Chemometric Methods for Determining Caffeine Content in Robusta Coffee as Alternative Standardization Techniques - Theodorus Rexa Handoyo; Riesta Primaharinastiti; Mochammad Yuwono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
There is a necessity for standardization to uphold coffee quality due to its frequent production and consumption. High-performance liquid chromatography (HPLC) serves as the benchmark for caffeine analysis in coffee in Indonesia. However, its high cost has prompted the exploration of alternative methods. This study aims to obtain a suitable alternative method for determining the caffeine content in robusta coffee as an effort toward standardization. Employing statistical and mathematical techniques in chemistry, chemometrics emerges as a promising alternative in analyzing caffeine in coffee. The approach was integrated with an ultraviolet (UV) spectrophotometer capable of analyzing substances across wavelengths from 200 to 400 nm. From the five replications, the HPLC method showed a caffeine content of 1.435 ± 0.011% (w/w), while the spectrophotometer showed a content of 1.723 ± 0.003% (w/w). Through the partial least squares regression (PLSR) and principal component regression (PCR) methods in RStudio, the results obtained were 1.432 ± 0.003% and 1.430 ± 0.002% (w/w), respectively. These results indicate good REP values of 0.022% for PLSR and 0.155% for PCR. With these findings, it is hoped that chemometrics can become an alternative method for analyzing caffeine in coffee.